Why They Eat What They Eat: Comparing 18 Eating Motives Among Omnivores and Veg*ns - Müssig, Markus; Pfeiler, Tamara M.; Egloff, Boris (Frontiers in Nutrition, 2022)
While the diets of most people include meat, millions of individuals follow a meat-free diet. But why do people eat what they eat? Here we explored differences and commonalities in the eating motives of omnivores and veg*ns (i.e., both vegetarians and vegans). Specifically, we compared mean levels and rank order of 18 eating motives in two samples (Study 1: 294 omnivores, 321 veg*ns; Study 2: 112 omnivores, 622 veg*ns). We found that omnivores were more motivated than veg*ns by the eating motives of Traditional Eating and Habits, while veg*ns were more motivated by Animal Protection and Environmental Protection. Differences among groups in Health were inconsistent across studies. Despite these differences in mean levels, the rank order of the eating motives was very similar: Two of the top four eating motives of both diet groups in both studies were Liking and Health, while Social Norms, Social Image, and Religion were among the four least important motives of both groups. Overall, while we did find differences in the absolute importance of certain motives, we also found striking similarities in the relative importance of eating motives, suggesting that including a wide range of eating motives could be beneficial when examining dietary behaviors.